1993
DOI: 10.1038/hdy.1993.117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype on chromosome variation in tissue culture of inbred and outbred rye

Abstract: To examine the effect of genotype on the nature of the cytological variation induced in culture, plants were regenerated from cultured immature embryos of six genotypes (lines A-F) of rye (Secale cereale L.). The variation observed differed among the six lines and was generally consistent with the donors. Regenerants of line A were consistent with the donor, cv. Ailés, in that chromosome translocations appeared at high frequencies. No structural or numerical variation was observed in the B chromosomes of line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The frequency of chromosomal changes is affected by different aspects of tissue culture, such as species (Bayliss 1973, Novak 1981, Kirti et al 1991, Linacero et al 1992a, b, Kidwell et al 1993, genotype (Li et al 1989, Amberger et al 1992, Cheng et al 1992, Thorn 1992, Molina et al 1992, Puolimatka et al 1993, culture medium (Wilkinson et al 1987, Amberger et al 1992, Linacero et al 1992a, b, Ghaemi et al 1993, genotype-culture medium interaction (Wilkinson et al 1987), the origin of meristematic organised growth from disorganised growth and the time spent in this state (Rhodes et al 1986, Lee et al 1987, Qureshi et al 1992, Karp 1995 and the concentration and type of plant growth regulators (Bai and Knott 1993).…”
mentioning
confidence: 99%
“…The frequency of chromosomal changes is affected by different aspects of tissue culture, such as species (Bayliss 1973, Novak 1981, Kirti et al 1991, Linacero et al 1992a, b, Kidwell et al 1993, genotype (Li et al 1989, Amberger et al 1992, Cheng et al 1992, Thorn 1992, Molina et al 1992, Puolimatka et al 1993, culture medium (Wilkinson et al 1987, Amberger et al 1992, Linacero et al 1992a, b, Ghaemi et al 1993, genotype-culture medium interaction (Wilkinson et al 1987), the origin of meristematic organised growth from disorganised growth and the time spent in this state (Rhodes et al 1986, Lee et al 1987, Qureshi et al 1992, Karp 1995 and the concentration and type of plant growth regulators (Bai and Knott 1993).…”
mentioning
confidence: 99%
“…It is known that changes in DNA can occur during in vitro culture (Cecchini et al 1992;Zheng 1991;Puolimatka and Karp 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Numerical and structural chromosome variation can be induced in tissue cultures of rye (Secale cereale L.) and the cytological variation is genotype dependent (Puolimatka and Karp 1993). In this study, the constant C-banding karyotype observed in all plants regenerated from the same Genome Downloaded from www.nrcresearchpress.com by University of Waterloo on 11/18/14…”
Section: Resultsmentioning
confidence: 99%